Highly active TiO2-based photocatalaysts for indoor air remediation - Puddu, Valeria (2008)
Energy saving policies applied to modem buildings and air recirculation systems promote the build up of high levels of VOCs in indoor air. The growing concern related to the air quality in indoor environments requires the replacement of ineffective traditional purification methods, with an efficient and cost effective technology. Photocatalytic oxidation that utilise TiO2, represents a promising candidate for this purpose. However, the formulation of photocatalysts that can efficiently utilise a sustainable energy source (i.e. solar light), still represents an ambitious target in this field.